2004
DOI: 10.1111/j.1346-8138.2004.tb00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Basal Cell Carcinomas Arising in a Port‐Wine Stain with a Remote History of Therapeutic Irradiation

Abstract: The coexistence of a basal cell carcinoma and a port-wine stain is a very rare condition that may be associated with previous treatments. We present a case of multiple basal cell carcinomas developing within the boundaries of a port-wine stain, which had been treated with a tholium X and argon laser. Our case suggests that port-wine stains which were previously treated with irradiation or argon laser should be examined carefully and regularly by both physician and patient, because they may hide basal cell carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…[7][8][9] The development of lasers and their ability to selectively target PWS blood vessels offered an improved treatment option. 7,10 …”
Section: History Of Pws Laser Treatmentmentioning
confidence: 99%
“…[7][8][9] The development of lasers and their ability to selectively target PWS blood vessels offered an improved treatment option. 7,10 …”
Section: History Of Pws Laser Treatmentmentioning
confidence: 99%
“…A number of long-term studies have revealed a significantly increased rate of various malignancies, including BCCs, in patients who underwent radiotherapy for hemangiomas. 8,9,12,13 As well, numerous case reports have documented BCCs arising at sites of previously irradiated tinea capitis, 14 port-wine stains, 15,16 and hemangiomas. 17,18 In these reports, BCCs typically arose 10 to 50 years after low-dose irradiation of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…8,24,25 Although, X-rays and thorium radiation have a relatively low carcinogenic risk, several cases of BCC as a late complication of their use in patients with PWS were reported in the literature. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Indeed, in 1946, McKee and Cipollaro 7 already wrote: 'To cause an obliterating endarteritis in telangiectasia, spider naevus and port-wine mark, requires an amount of treatment that will seriously injure normal tissue.' The long-term neoplastic potential of medical irradiation has since been well established, 9,17,18,[23][24][25][26] and X-rays, radium, thorium and other sources of radiotherapy are no longer a treatment of choice in patients with vascular dermatoses.…”
Section: Discussionmentioning
confidence: 99%
“…BCC arising in a PWS or nevus flammeus is a rare finding, although reports date back to the last quarter of the radiotherapy era 9–23 . The present prospective evaluation for the presence of signs of BCC in patients being treated in our centre for PWS was prompted by the increasing number of publications suggesting a connection between these entities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation